[President Warren Baker receives donation from Unocal, July 2000] (2000)
Warren J. Baker standing at left. Speaking at podium is Unocal Vice President Mark Smith. The $5.6 million cash gift from Unocal Corporation was one of the largest contributions to Cal Poly in the university's history at the time. The donation was targeted for research aimed at developing environmentally sensitive technology to aid petroleum companies in restoring contaminated sites. The donation was presented on July 6 to the College of Science and Mathematics and the Environmental Biotechnology Institute.